DETERMINANTS OF DIARRHEA EVENTS ON UNDER FIVE CHILDREN IN HARAPAN RAYA PUBLIC HEALTH CENTER WORKING AREA 2019 - christine vita purba; christine vita gloria (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2019)
Diarrhea is defecation accompanied by liquid (diarrhea). It can even be iust liquid which is more often than usual (3 times or more in a day) can be accompanied by symptoms of dehydration, fever, nauseous vomit, weak, pale, eye sunken. This research was quantitative analytic with cross sectional design. It was done by distributing questuionnaires to 100 respondents by purposive sampling. The location of this research was conducted in the working area of Harapan Raya Public Health Center in may-june 2019 with population of children under five 6215 people. The incidence of diarrhea in children under five isÂ highest with 19,2% of people. The purpose of this study was to find the determinants of diarrhea in children under five in the working area of the Harapan Raya Public Health Center in 2019. The results of the study showed the relationship between exclusive breast milk, bottle hygiene, handwashing habits with soap, food storage. The results of the study concluded that exclusive breat milk, bottle hygiene, handwashing habits with soap, food storage were determinats of diarrhea event in children under five in the working area of Harapan Raya Public Health Center 2019. And it is expected to be able to prevent diarrheal diseases in children under five by implementing exclusive breastfeeding, maintain higinic feeding bottles properly, do hand washing with soap properly, and have a safe storage area to eat amimals.